Assessment of the advantage of the serum S100B protein biomonitoring in the management of paediatric mild traumatic brain injury—PROS100B: protocol of a multicentre unblinded stepped wedge cluster randomised trial. Issue 5 (24th May 2019) - Bouvier, Damien; Balayssac, David; Durif, Julie; Mourgues, Charline; Sarret, Catherine; Pereira, Bruno; Sapin, Vincent
Abstract : Introduction: S100B serum analysis in clinical routine could reduce the number of cranial CT (CCT) scans performed on children with mild traumatic brain injury (mTBI). Sampling should take place within 3 hours of trauma and cut-off levels should be based on paediatric reference ranges. The aim of this study is to evaluate the utility of measuring serum S100B in the management of paediatric mTBI by demonstrating a decrease in the number of CCT scans prescribed in an S100B biomonitoring group compared with a 'conventional management' control group, with the assumption of a 30% relative decrease of the number of CCT scans between the two groups. Methods and analysis: The protocol is a randomised, multicentre, unblinded, prospective, interventional study (nine centres) using a stepped wedge cluster design, comparing two groups (S100B biomonitoring and control). Children in the control group will have CCT scans or be hospitalised according to the current recommendations of the French Society of Paediatrics (SFP). In the S100B biomonitoring group, blood sampling to determine serum S100B protein levels will take place within 3 hours after mTBI and subsequent management will depend on the assay. If S100B is in the normal range according to age, the children will be discharged from the emergency department after 6 hours' observation. If the result is abnormal, CCT scans or hospitalisation will be prescribed in accordance with current SFP recommendations. The primary outcome measure will be the proportion of CCT scans performed (absence/presence of CCT scan for each patient) in the 48 hours following mTBI. Ethics and dissemination: The protocol presented (Version 5, 03 November 2017) has been approved by the ethics committee Comité de Protection des Personnes sud-est 6 (first approval 08 June 2016, IRB: 00008526). Participation in the study is voluntary and anonymous. The study findings will be disseminated in international peer-reviewed journals and presented at relevant conferences. Trial registration number: NCT02819778 .